2018
DOI: 10.22159/ajpcr.2018.v11i8.25220
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram Profiling of Helicobacter Pylori Strains and the Efficacy of Brassica Capitata Against Resistant Strains Isolated From the Patients Suffering From Gastroduodenal Diseases in Gauhati, Assam

Abstract: Objective: Helicobacter pylori resistance toward commonly used antibiotics is increasing leading to the treatment failure; hence, our aim is to determine the antibiogram susceptibility pattern of H. pylori strains isolated from Guwahati, Assam (Northeast India) and also to test the efficacy of the Brassica capitata against the multi and dual drug-resistant strains of North and Northeast India.Methods: Minimum inhibitory concentration of different antibiotics was determined by agar dilution method. Disc diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Mtz R is high (66%-92.4%) in all six regions of India except Assam (27.2%) 13 and Mumbai (16.7%) 20 and Maastricht III consensus conference suggests that the efficacy of metronidazole reduces if >40% of the population is resistant. 31 However, Mtz R has a limited impact on actual treatment efficacy because of a frequent disconnect between in vitro with in vivo results and the synergistic compensation by other co-administered drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mtz R is high (66%-92.4%) in all six regions of India except Assam (27.2%) 13 and Mumbai (16.7%) 20 and Maastricht III consensus conference suggests that the efficacy of metronidazole reduces if >40% of the population is resistant. 31 However, Mtz R has a limited impact on actual treatment efficacy because of a frequent disconnect between in vitro with in vivo results and the synergistic compensation by other co-administered drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The highest resistance was noticed in West India with 72.5% (58/80). A high rate of resistance was also observed in South India (42.4%, 183/432) followed by Central India (38.4%,10/26) [13], North India (31.01%, 89/278) and East India (1%, 1/99). In contrast, North-Eastern parts of India have found a 0% rate of resistance (Table 2).…”
Section: Areamentioning
confidence: 91%
See 2 more Smart Citations
“…De et al showed the good efficacy of curcumin in H. pyloriinfected mouse [33]. Our other studies have shown that the methanolic extract of Paederia foetida [34], methanolic and ethanolic extract Parmelia perlata [35], Embilica officinalis [36], and methanolic and n-hexane extract of Brassica capitata is effective against dual and multidrug resistance H. pylori stain [37]. Our various studies prompted us to explore the efficacy of M. coreia, which is being extensively cultivated in India for the dye which is obtained from the root bark and it is a popular medicinal plant in Thailand.…”
Section: Discussionmentioning
confidence: 99%